P119: B-mode point-of-care ultrasound without doppler may help include or exclude significant carotid stenosis in stroke and transient ischemic attack patients - a prospective pilot study. (2nd June 2016) - Simard, R.; Socransky, S.
Abstract : Introduction: Emergency physicians can use B-mode Point-of-Care Ultrasound (POCUS) to identify a patient's carotid vasculature including the common carotid artery (CCA), and carotid bulb (CB) as well as carotid bifurcation into the internal carotid artery (ICA) and external carotid artery (ECA). Radiology performed carotid ultrasound (RPCU) is performed using both B-mode and spectral Doppler ultrasound, a combination termed "duplex" ultrasound where first arteries are evaluated for stenosis using B-mode ultrasound, which is followed by flow measurements using Doppler. Performing flow measurements using Doppler may add a significant amount of time to the ultrasound, which makes it impractical for an emergency physician in a busy emergency department. Some institutional practices include arranging for outpatient RPCU to assess patients with Transient Ischemic Attack (TIA) and have them follow up in an outpatient TIA clinic. This study explored whether B-mode POCUS without Doppler may help identify Stroke or TIA patients in the emergency department with significant carotid stenosis (CS) by measuring the CCA, CB, and ICA lumen.Methods: Adult patients with an emergency physician diagnosis of stroke or TIA who were sent for RPCU were included in this study. An emergency medicine resident in their POCUS fellowship training performed a B-mode POCUS of the patient's right and left CCA, CB and ICA with the patient sitting 90 degrees. Three measurements of each of the 3 sections were obtained and the mean calculated. This was then compared to the results from the RPCU as CS >50% or CS <50%.Results: 38 patients were included in the study between February and June 2013. We observed a correlation between absolute differences in comparing the right side of the carotid vasculature to the left side of the carotid vasculature with CS >50%. Also, in one case, the absolute lumen diameter with B-mode POCUS without Doppler predicted near complete CS which was confirmed on the RPCU.Conclusion: B-mode POCUS without Doppler may be useful in identifying patients with CS above and below 50% and may help identify patients who need expedited referrals for CS. However, further research is required before this method can be recommended.